Correlation of the Mastoid Pneumatization and Bone Destruction in CSOM with Acquired Cholesteatoma using Computed Tomography - Dyah Nilasari; Farah H Ningrum; Zulfikar Naftali (Journal of Agromedicine and Medical Sciences, 2016)
Chronic Suppurative Otitis Media (CSOM) is still a public health problem especially in developing countries. CSOM with acquired cholesteatoma accompanied referred to as the type of hazard, as they often lead to dangerous complications and have a high rate of morbidity and mortality. Mastoid CT with 0,625mm slice thicness may reveal detail cholesteatoma and bone destruction. It’s an analytic observational study with cross sectional design. This study consisted of 30 cases CSOM, aged 18-60 years and had a 0,625mm slice thicness CT scan mastoid examinations in Dr. Kariadi Hospital Semarang and indicating a cholesteatoma and bone destructions. The result showed that hypopneumatization type and mild degree of bone destructions obtained in most subjects, each 20 and 21, but there’s no correlation between mastoid pneumatization and bone destruction (p 0,367 or p > 0,05). This study showed more lower type of the mastoid pneumatization, more severe degree of bone destructions.Keywords: CSOM, mastoid pneumatization, Mastoid CT